Drug-Coated Balloon vs. Stent for de novo Non-small Coronary Artery Disease: A Systematic Review and Meta-Analysis - Sun, Kaiwen; Liu, Zhenzhu; Wang, Hongyan (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Drug-coated balloon (DCB) has been an attractive option in de novo vessels. A systematic review and meta-analysis were conducted to evaluate the efficacy and safety of DCB vs. stent for treating de novo lesions in non-small vessels. Methods: Studies in PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science were searched (from their commencement to March 2021). This meta-analysis was performed by Review Manager 5.3. Results: A total of 3 random controlled trials (RCTs) with 255 patients and 2 observational studies (OS) with 265 patients were included in this meta-analysis following our inclusion criteria. It could be observed that DCB presented no significant difference in cardiac death (CD) (RR 0.33, 95% CI [0.01, 8.29], p = 0.50 in OS), myocardial infarction (MI) (RR 0.49, 95% CI [0.09, 2.50], p = 0.39 in RCT), target lesion revascularization (TLR) (RR 0.64, 95% CI [0.19, 2.18], p = 0.47 in RCT) (RR 1.72, 95% CI [0.56, 5.26], p = 0.34 in OS), and late lumen loss (LLL) (SMD −0.48, 95% CI [−1.32, 0.36], p = 0.26 in RCT) for de novo non-small coronary artery disease (CAD) compared with stents, whereas minimal lumen diameter (MLD) including MLD1 (SMD −0.67, 95% CI [−0.92 −0.42], p < 0.00001 in RCT) and MLD2 (SMD −0.36, 95% CI [−0.61 −0.11], p = 0.004 in RCT) was smaller in DCB group. Conclusion: This systematic review showed that DCB might provide a promising way on de novo non-small coronary artery disease compared with stents. However, more RCTs are still needed to further prove the benefits of the DCB strategy. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/#recordDetails.